2002
DOI: 10.1094/phyto.2002.92.9.976
|View full text |Cite
|
Sign up to set email alerts
|

Improving Biological Control by Combining Biocontrol Agents Each with Several Mechanisms of Disease Suppression

Abstract: Two biocontrol agents, a yeast (Pichia guilermondii) and a bacterium (Bacillus mycoides), were tested separately and together for suppression of Botrytis cinerea on strawberry leaves and plants. Scanning electron microscopy revealed significant inhibition of Botrytis cinerea conidial germination in the presence of Pichia guilermondii, whereas Bacillus mycoides caused breakage and destruction of conidia. When both biocontrol agents were applied in a mixture, conidial destruction was more severe. The modes of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
110
0
10

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(126 citation statements)
references
References 21 publications
6
110
0
10
Order By: Relevance
“…In the last few years, several reports have shown that co-inoculation of beneficial microorganisms could stimulate plant growth and/or increase plant disease resistance relative to inoculation with a single biocontrol agent (Raimam et al, 2007;Whipps, 2004). Although such combinations may enhance the level of plant protection against pathogen attack (Ezziyyani et al, 2007;Guetsky et al, 2001Guetsky et al, , 2002, the possible competitiveness between these micro-organisms has to be taken into consideration (Alabouvette et al, 2006). …”
Section: Interaction With Other Biocontrol Agentsmentioning
confidence: 99%
“…In the last few years, several reports have shown that co-inoculation of beneficial microorganisms could stimulate plant growth and/or increase plant disease resistance relative to inoculation with a single biocontrol agent (Raimam et al, 2007;Whipps, 2004). Although such combinations may enhance the level of plant protection against pathogen attack (Ezziyyani et al, 2007;Guetsky et al, 2001Guetsky et al, , 2002, the possible competitiveness between these micro-organisms has to be taken into consideration (Alabouvette et al, 2006). …”
Section: Interaction With Other Biocontrol Agentsmentioning
confidence: 99%
“…Although several possible mechanisms have been reported (Droby and Chalutz, 1994;Janisiewicz and Korsten, 2002;Massart and Jijakli, 2007), the main mode of action of yeast(-like) biocontrol agents is believed to be competition for nutrients and space (Droby and Chalutz, 1994;Lima et al, 1997;Janisiewicz et al, 2000;Castoria et al, 2001). According to the literature dealing with competition for nutrients and space using different antagonist/pathogen(/host) systems (Castoria et al, 1997(Castoria et al, , 2001Lima et al, 1997;Janisiewicz et al, 2000;Guetsky et al, 2002;Vero et al, 2002): (i) most studies have considered either the in vitro or the in situ approach but not both, (ii) the contribution of the competition for nutrients and competition for space has rarely been considered separately, and (iii) in situ assays have been often performed using the Nutrient Yeast Dextrose Broth medium whose composition is not comparable with that of host tissues. In the present study, competition for nutrients as a mode of action of A. pullulans strain Ach1-1 against P. expansum was first examined in vitro using a system that allows discrimination between competition for nutrients and that for space (Janisiewicz et al, 2000) using increasing concentrations of apple juice.…”
Section: Introductionmentioning
confidence: 99%
“…The stability of the control by the microorganism is usually associated with the performance of multiple mechanisms of action (Guetsky et al, 2001) and with an aggressive colonization of the tissues of the host plant (Kloepper & Beauchamp, 1992). In the present study, the mechanisms of action of the DFs1420 isolate were not studied here but some of its capabilities are already known.…”
Section: Biological Control Of Tomato Bacterial Spot By Seed Microbiomentioning
confidence: 97%